2016
DOI: 10.1021/acs.jproteome.6b00414
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Relative Quantitation of Isobaric and Isomeric Human Histone H2A and H2B Variants by Fourier Transform Ion Cyclotron Resonance Top-Down MS/MS

Abstract: Histone variants are known to play a central role in genome regulation and maintenance. However, many variants are inaccessible by antibody-based methods or bottom-up tandem mass spectrometry due to their highly similar sequences. For many, the only tractable approach is with intact protein top-down tandem mass spectrometry. Here, ultrahigh-resolution FT-ICR MS and MS/MS yield quantitative relative abundances of all detected HeLa H2A and H2B isobaric and isomeric variants with a label-free approach. We extend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 39 publications
(58 reference statements)
0
29
0
Order By: Relevance
“… 235 Advances in ETD-based methods are making significant inroads toward this goal, and three recent studies, all using front end ETD sources in various capacities, have noticeably improved the ability to analyze intact histones on chromatographic time scales. 236 238 Furthermore, Molden et al showed how combinations of bottom-up and top-down approaches can comprehensively profile histone changes. 239 …”
Section: Cases Where Etd Is Particularly Helpfulmentioning
confidence: 99%
See 1 more Smart Citation
“… 235 Advances in ETD-based methods are making significant inroads toward this goal, and three recent studies, all using front end ETD sources in various capacities, have noticeably improved the ability to analyze intact histones on chromatographic time scales. 236 238 Furthermore, Molden et al showed how combinations of bottom-up and top-down approaches can comprehensively profile histone changes. 239 …”
Section: Cases Where Etd Is Particularly Helpfulmentioning
confidence: 99%
“…Perhaps the most straightforward quantitative approach is label-free quantitation, which has been a component of several ETD experiments discussed above. 85 , 120 , 203 , 234 , 236 Stable isotope labeling is another widely used approach to enable multiplexed quantitation, and several strategies can be employed to incorporate stable isotopes into samples. 352 ETD is readily coupled with MS 1 -based labeling approaches, including dimethyl labeling, stable isotope labeling in amino acid cell culture (SILAC), and neutron-encoded (NeuCode) SlLAC.…”
Section: Other Uses Of Etd and Related Ion–ion Reactionsmentioning
confidence: 99%
“…Histones H2A.Z and H3.3 may destabilize nucleosomes (for example, see Jin and Felsenfeld 2007) and thus facilitate transcription. In considering the presence of the human histone variants at promoters, it may be useful to note that H3.3 constitutes ∼10% of the total histone H3 species and that H2A.Z is ∼1%-3% of the total H2A species (Dang et al 2016). Hence, the presence of H3.3 and H2A.Z at promoters could provide some specificity to core promoter function, but their roles, if any, in the initiation of transcription remain to be determined.…”
Section: Chromatin Signals and Structurementioning
confidence: 99%
“…Likewise, standard MS/MS experiments, in which each ionized compound (precursor ion) in a sample is isolated before dissociation and detection of its fragment ions in the mass spectrometer, can be limited by overlapping isotopic distributions of different peptide or protein forms. Although isolation and fragmentation of a single histone isoform, as well as the label-free, direct localization and relative quantitation of histone and ribonucleic acid, modifications by MS/MS have been demonstrated, a more general approach that does not rely on precursor ion isolation would significantly advance all fields of PTM research.…”
Section: Introductionmentioning
confidence: 99%